(3GdGYJQGVGJ Ydi GdebGeGJs - (3CHh eMeO YHO Gddg Hf HQi Hf YHO GdLHGQ GdebOSi Gdfehis; (3GdbGSe Hf Ydj Hf eMeO Hf YKeGf, CHh eMeO GdMQjQj GdHUQj,J (B516 (3g` s
(3BNQgG (B:s
(3JfJgi HGdMOjK Yf GdGfJbGOGJ GdhGQOI Ydi BNQ GdebGeI GdSGHYI hGdKdGKjf s
(3fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3GSJOQGcs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs